Ultrahigh-efficiency aqueous flat nanocrystals of CdSe/CdS@Cd1−xZnxS colloidal core/crown@alloyed-shell quantum wells - Shendre, Sushant (2020)
Colloidal semiconductor nanoplatelets (NPLs) are highly promising luminescent materials owing to their exceptionally narrow emission spectra. While high-efficiency NPLs in non-polar organic media can be obtained readily, NPLs in aqueous media suffer from extremely low quantum yields (QYs), which completely undermines their potential, especially in biological applications. Here, we show high-efficiency water-soluble CdSe/CdS@Cd1−xZnxS core/crown@shell NPLs formed by layer-by-layer grown and composition-tuned gradient Cd1−xZnxS shells on CdSe/CdS core/crown seeds. Such control of shell composition with monolayer precision and effective peripheral crown passivation, together with the compact capping density of short 3-mercaptopropionic acid ligands, allow for QYs reaching 90% in water, accompanied by a significantly increased photoluminescence lifetime (∼35 ns), indicating the suppression of nonradiative channels in these NPLs. We also demonstrate the controlled attachment of these NPLs without stacking at the nanoscale by taking advantage of their 2D geometry and hydrophilicity. This is a significant step in achieving controlled assemblies and overcoming the stacking process, which otherwise undermines their film formation and performance in optoelectronic applications. Moreover, we show that the parallel orientation of such NPLs achieved by the controlled attachment enables directed emission perpendicular to the surface of the NPL films, which is highly advantageous for light extraction in light-emitting platforms.